Analisis Layanan Jaza Pospay terhadap Pengendalian Intern Atas Pendapatan PT.Pos Indonesia (Persero) KCP. AEK Kota Batu, Labuhanbatu Utara - Izzatul Zannah; Nurlaila Nurlaila (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
One of the most important objectives of internal control is to create good control within companies and cooperatives. In improving good systems and procedures. The purpose of this study was to determine the systems and procedures for paying bills with pospay points (sopp pos) in supporting internal control. This research was conducted using a case study at the post office in North Sumatra. This research uses descriptive qualitative method. Researchers then collect information through interviews, field observations, documentation and literature studies to confirm the information obtained. because of that While studying with Pospay you can pay various bills and fees, namely telephone bills Payment, electricity bills (PLN), electricity bills, drinking water bills (PDAM), Insurance, installment loans (financing), credit card loans and personal loans, credit enhancements, increased funds, TV subscriptions and others.